Circadian Rhythm Disruption and Alzheimer’s Disease: The Dynamics of a Vicious Cycle - Sharma, Ashish (Curr Neuropharmacol, 2021)
All mammalian cells exhibit circadian rhythm in cellular metabolism and energetics. Autonomous cellular clocks are modulated by various pathways that are essential for robust time keeping. In addition to the canonical transcriptional translational feedback loop, several new pathways of circadian timekeeping - non-transcriptional oscillations, post-translational modifications, epigenetics and cellular signaling in the circadian clock - have been identified. The physiology of circadian rhythm is expansive, and its link to the neurodegeneration is multifactorial. Circadian rhythm disruption is prevelant in contamporary society where light-noise, shift-work, and transmeridian travel are commonplace, and is also reported from the early stages of Alzheimer's disease (AD). Circadian alignment by bright light therapy in conjunction with chronobiotics is beneficial for treating sundowning syndrome and other cognitive symptoms in advanced AD patients. We performed a comprehensive analysis of the clinical and translational reports to review the physiology of the circadian clock, delineate its dysfunction in AD, and unravel the dynamics of the vicious cycle between two pathologies. The review delineates the role of putative targets like clock proteins PER, CLOCK, BMAL1, ROR, and clock-controlled proteins like AVP, SIRT1, FOXO, and PK2 towards future approaches for management of AD. Furthermore, the role of circadian rhythm disruption in aging is delineated.